Pembangunan Kandis Resource Centre - pemangkin pelancongan pendidikan - Fikri, Afandi (2007)
Today, tourism industry in Malaysia gives a second importance economy contribution to Malaysia. In the tourism industry, there are many types of toursim including culture and heritage tourism. Thus, through this tourism, it also can catalyst the educational tourism. The researcher has made a research about the development of Kandis Research Centre as a catalyst in the tourism educational by looking the potential of KRC and what are the factors that influence visitors or tourists to visit KRC. Some of attibutions have been found from the past case studies and from the interviewing with the respondents. A qualitative method was used, with interviews using open-ended questions with those which have connetions with KRC, in the tourism industry and the the agency which involves with educational tourism. The technique such as Importance- Performance Analysis (IPA) was used to analyze the attributions attraction at KRC, which the interpretations were made by using Matrix Importance – Performance that was divided into 4 quadrants. In conclusion, the researcher has concluded that the development of KRC can be seen in a quadrant form, the successful of development of KRC depends on internal and external factors, the condition of KRC can be seen based on destination of life cycle – Butler Sequence Model and general suggestions also been suggested in this report in order to attract more visitors and tourists to visit KRC.